Students' growth mindset: Relation to teacher beliefs, teaching practices, and school climate. (August 2022) - Yu, Junlin; Kreijkes, Pia; Salmela-Aro, Katariina
Abstract: To effectively cultivate students' growth mindset, it is important to identify contextual factors that may communicate mindset messages to students. The present study examined the association of students' growth mindset with various dimensions of teacher beliefs (mindset, self-efficacy), teaching practices (guided inquiry, group work, task differentiation, in-class ability grouping, mastery and normative evaluations), and school climate (holistic development, in-school ability grouping). Participants were 2200 ten-year-old students, 358 teachers, and 65 principals from Finnish elementary schools that participated in the OECD Survey on Social and Emotional Skills. Multilevel analyses show that students endorsed more of a growth mindset in classrooms where teachers used guided inquiry and in schools that emphasized students' social-emotional development. In contrast, students endorsed more of a fixed mindset when teachers assigned different tasks to different students based on ability. Implications for how to combine teaching practices to support students' growth mindset are discussed. Highlights: Teacher and school factors linked to students' mindset were identified. Teachers' mindset and efficacy were not directly associated with students' mindset. Students had a stronger growth mindset when teachers used guided inquiry. Students had a stronger fixed mindset when teachers differentiated tasks by ability. Students had a stronger growth mindset in schools that valued holistic development.